Phytochemical Analysis, In Vitro Anti-Inflammatory and Antimicrobial Activity of Piliostigma thonningii Leaf Extracts from Benin - Marquardt, Peter; Vissiennon, Cica; Schubert, Andreas; Birkemeyer, Claudia; Ahyi, Virgile; Fester, Karin (Planta Medica, 2020)
The leaves of Piliostigma thonningii are used in traditional medicine in Benin to treat inflammatory skin diseases and infections. So far, pharmacological studies of the anti-inflammatory and anti-infective effects of phytochemically characterized extracts of P. thonningii have been very limited. Therefore, we investigated the in vitro anti-inflammatory and antimicrobial effect of P. thonningii leaf extracts and analyzed the phytochemical composition of extracts of different polarities (water, 50% ethanol, and n-hexane). Quercetin-3-O-rhamnoside was confirmed as the main flavonoid in the polar extracts. GC-MS analysis identified 20 constituents of the aqueous extract and 28 lipophilic compounds of the n-hexane extract by comparison with authentic standards and spectral library data. The aqueous P. thonningii leaf extract inhibited the IL-8 and IL-6 secretion in TNF-α-stimulated HaCaT cells in a concentration-dependent manner with IC50 values of 74 µg/mL for IL-8 and 89 µg/mL for IL-6. However, an inhibitory effect of the identified quercetin-3-O-rhamnoside and its aglycone, quercetin, on the release of IL-8 and IL-6 could not be demonstrated. In the antimicrobial screening, inhibition zones for a 50% EtOH leaf extract of P. thonningii were found for Staphylococcus epidermidis, Staphylococcus aureus, methicillin-resistant Staphylococcus aureus, and Escherichia coli. For none of the microbial strains, however, the MIC was below 500 µg/mL, so that the antibacterial activity must be classified as low. As a result, our investigations primarily support the ethnomedical use of P. thonningii leaf extracts in topical inflammatory conditions. Further studies are required to identify the compounds responsible for the in vitro anti-inflammatory effects.
Keywords: Piliostigma thonningii; Fabaceae; inflammation; antimicrobial; HaCaT